Comparison of Properties of Admicellar Polymerization Surface Modified Silica- and Conventional Fillers-Reinforced Tyre Tread Compounds - Toh-Ae, P.; Pongprayoon, T.; Lopattananon, N.; Sahakaro, K. (Asian Journal of Chemistry, 2013)
Silanol groups on a silica surface lead to strong hydrogen bonding between the silica particles and aggregates, resulting in a poor dispersion of silica in rubber compounds. This study improved the compatibility between silica and rubber by coating the silica surface with a polyisoprene film using an admicellar polymerization technique. The modified silica was characterized by Fourier-transform infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy. A comparison of the properties of natural rubber compounds filled with modified silica, silica with silane, carbon black and a mixed filler of silica and carbon black showed that the silica-silane filled compound exhibited the highest mixing torque and Mooney viscosity, whereas the modified silica-filled compound exhibited the lowest values. The silica-silane filled vulcanizates showed a higher modulus, reinforcing index, hardness and abrasion resistance than the vulcanizates containing modified silica. On the other hand, the modified silica-filled vulcanizates exhibited excellent ultimate tensile properties. The loss tangent at 0 ºC and 60 ºC of the vulcanizates filled with different types of fillers as well as filler dispersion are also discussed.